Perbandingan Kinerja Bumdes Yang Terdaftar Dan Tidak Terdaftar Sebagai Badan Hukum - Ariatiningsen; Aslamiyah, Nurul; Qolbiyyah, Shofwatal (Institut Agama Islam Negeri Ponorogo, 2024)
This research explores the comparison of the performance of Village-Owned Enterprises (BUMDes) that are registered as legal entities and those that are not registered, with a focus on the impact of legality on operational effectiveness and economic contribution to village communities. Registration of BUMDes as a legal entity is believed to provide various benefits, such as easier access to funding sources, increased public trust, and more transparent business management. This research uses mixed methods yuridis normative and by collecting qualitative data through interviews and field observations. The results of the analysis show that BUMDes registered as legal entities tend to have superior performance in terms of revenue, operational efficiency and business expansion capabilities. Meanwhile, unregistered BUMDes face limited access to funding and strategic partnerships, as well as problems in terms of accountability and transparency. This study suggests the importance of government support in facilitating the legal entity registration process for BUMDes in order to increase competitiveness and sustainability at the village level.